In Vitro Anthelmintic Activity of Benincasa Hispida (Petha) Thunb Leaves - CHIRANJIB BHATTACHARJEE; DEBJIT B; PANKAJ TIWARI; K.K. TRIPATHI; A.S.DUTTA (International Journal of Pharma and Bio Sciences, 2010)
The present study was undertaken to evaluate anthelmintic activity of crude aqueous, Petroleum ether, chloroform and Methanol extract of Benincasa hispida (Petha) leaves using Pheretima posthuma as test worms. Single concentration (5 %) of extracts was tested in the bioassay, which involved determination of time of paralysis (P) and time of death (D) of the worms. Piperazine citrate was included as standard reference and distilled water as control. The results of present study indicated that Benincasa hispida (Thunb) fresh leaves extracts were exhibited anthelmintic activity significantly (***p<0.001) when compared with standard (Piperazine citrate) group. Chloroform extract (30.6 ± 1.364 minutes & 56.8 ± 1.497 minutes) and petroleum ether extract (55.8 ± 2.518 minutes & 80.4 ± 2.909 minutes) showed shortest time of paralysis (P) and death (D) with 50 mg/ml concentration respectively among all extracts. Whereas, in control group, worms were observed for 24 hours and no paralysis or death was found during that period. Further studies are in process to isolate the active principle/s responsible for the activity.